Indian Pediatric Oncology Group (InPOG) - Collaborative research in India comes of age - Ramandeep Singh Arora; Sameer Bakhshi (Elsevier, 2016)
Treatment of children with cancer on clinical trials, often in the context of national and international co-operative groups, is one of the cornerstones of pediatric oncology treatment and has been shown to improve outcomes of children with cancer. While enrolling children with cancer in prospective multi-centre trials has become the norm in high-income countries, it has remained an exception in low and middle-income countries until recently. In this article, we briefly review the global landscape of pediatric oncology co-operative groups and then discuss the Indian scenario including more recent developments of the formation and galvanization of the Indian Pediatric Oncology Group (InPOG). The mission of InPOG is to improve the outcomes of children with cancer in India by collaborative research. A roadmap for the development and conduct of an InPOG study has been created and 21 disease-specific subcommittees have been formed. Multi-centre studies on Hodgkin lymphoma and acute lymphoblastic leukemia are currently recruiting and several others are under development.